The linkage between microRNA and cancer and its delivery as cancer therapy: A mini-review: microRNA and its delivery as cancer therapy - Syed Najmuddin, Syed Umar Faruq; Kamarudin, Ammar Akram; Abdul Sani, Suraya; Norrrahim, Mohd Nor Faiz; Abdul Latif, Nur ’Atikah; Wah, Lucky Goh Poh (Cellular and Molecular Biology, 2023)
The central dogma of molecular biology was no longer "central" after ground-breaking discoveries conveyed gene expression involves more complex physiological functions in cancer pathogenesis over the last decade. MicroRNAs (miRNAs) are short non-coding RNA that regulate gene expression, affecting key molecular pathways involved in sustaining the proliferative signalling for tumour development, evasion of cellular death, invasion, angiogenesis, as well as metastasis in a plethora of cancer types. MiRNA expression is dysregulated in human cancer through a number of processes, including miRNA gene amplification or deletion, faulty miRNA transcriptional regulation, dysregulated epigenetic alterations, and flaws in the miRNA biogenesis machinery. As a result, the current progress of treatment intervention focuses on modifying the miRNA levels in cancer therapeutics. Nevertheless, the mode of delivery and current management of miRNA therapies remains one of the many questions that need to be addressed. Here, we provided a comprehensive mini-review outlining the role of miRNA in cancer as well as its mode of delivery which includes liposomes, viral vectors, inorganic material-based nanoparticles, and cell-derived membrane vesicles. Likewise, the regulation of miRNA in other diseases and their challenges in translational research was also thoroughly discussed.